2006
DOI: 10.1139/l06-101
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pressure fluctuations on sloping stilling basins

Abstract: Various types of hydraulic jump occurring on horizontal and sloping channels have been analyzed experimentally, theoretically, and numerically and the results are available in the literature. In this study, artificial neural network models were developed to simulate the mean pressure fluctuations beneath a hydraulic jump occurring on sloping stilling basins. Multilayers feed a forward neural network with a back-propagation learning algorithm to model the pressure fluctuations beneath such a type of hydraulic j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…NNs are relatively stable with respect to noise in data and have a good generalization potential, to represent inputoutput relationships [11]. Once a NN model is trained for its generalization properties, it can be demonstrated that the trained model represents the physical process of the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NNs are relatively stable with respect to noise in data and have a good generalization potential, to represent inputoutput relationships [11]. Once a NN model is trained for its generalization properties, it can be demonstrated that the trained model represents the physical process of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge acquired for the problem domain during the training process is encoded within the NN in two forms: (a) in the network architecture itself (through number of hidden units), and: (b) in a set of constants, or weights [12]. Although there are several attempts in other scientific branches that have shown, that useful information could be obtained from trained neural networks (see Yao [12] for relevant references), limited research has been done for water-engineering applications [11,13]. * corresponding author; e-mail: agunal@gantep.edu.tr This study focuses on modelling of three unit hydrograph parameters, namely, the peak discharge q p , the time to peak discharge t p , and the time base of unit hydrograph t b , based on the most relevant hydrological and geomorphological variables.…”
Section: Introductionmentioning
confidence: 99%
“…), which are especially attractive for modeling processes. However, adequate knowledge about the physics of these techniques is limited [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The question is: How can one apply this kind of model in any other study, while the model has not been formulated? Recent studies, such as Khorchani & Blanpain (2005) and Guven et al (2006) in the civil engineering literature, have been seen to overcome this problem by providing the explicit formulation on which the neural network system is based.…”
Section: Introductionmentioning
confidence: 99%